2018
DOI: 10.1002/nau.23871
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on reporting outcomes and outcome measures in trials on synthetic mesh procedures for pelvic organ prolapse: Urgent action is needed to improve quality of research

Abstract: The use of synthetic mesh in pelvic organ prolapse surgery is being closely scrutinized because of serious concerns regarding life‐changing complications such as erosion, pain, infection, bleeding, dyspareunia, organ perforation, and urinary problems. Randomized trials and their syntheses in meta‐analysis offer a unique opportunity to assess efficacy and safety. However, outcomes and outcome measures need to be consistently selected, collected, and reported across randomized trials to be effectively combined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
3
23
0
2
Order By: Relevance
“…Since April 16, 2019, there have been no FDA‐approved surgical mesh products for transvaginal repair marketed for use in the United States. POP procedures using synthetic mesh require additional attention because of possible complications . According to Biler et al, 1‐year follow‐up time can be too short for the development of mesh erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Since April 16, 2019, there have been no FDA‐approved surgical mesh products for transvaginal repair marketed for use in the United States. POP procedures using synthetic mesh require additional attention because of possible complications . According to Biler et al, 1‐year follow‐up time can be too short for the development of mesh erosion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study looked at the reporting outcome measures in trials on synthetic mesh procedures for POP and concluded that urgent action is needed to improve the quality of research in this field [32]. Of the 71 randomized trials, 24 different types of mesh were identified.…”
Section: Strengths Limitations and Areas Of Future Researchmentioning
confidence: 99%
“…The impact on individual patients but also on clinical practice and research is therefore highly variable. Wide variations of reported outcomes and outcome measures in POP research have also been documented 14,15 . One of the consequences is a failure to acquire high‐quality data, affecting the quality of available evidence, and clinical guidance and practice.…”
Section: Introductionmentioning
confidence: 99%